(3YQGFS GdZQQ hZQGFS GdacQ aj CMcGe GdfXQs - (3YdhGf Hf YWjI GdgjJjs ((3YHO GdhgGH Hf SdjeGf GdghT s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CeG HYO abO SCdfi HYV GdCUMGH hGdJeS efi HYV GdWdGH JQJjH QSGdI ajeG YeJ Hg GdHdhi ai GdCeUGQ hGdbQi ef EWdGb GdHUQ s
(3BNQgG (B:s
(3hgPG BNQ eG CQOfG JHjGfg hbUOfG EJbGfg ef GdQSGdI hGdCHhGH hNJe GdaUhd hNJe GdcJGH hSejJgG YQGFS GdZQQ hZQGFS GdacQ ai CMcGe GdfXQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdESdGejs